2022
DOI: 10.1021/acsaem.2c01783
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heterocyclic Organic Compounds on the Optoelectronic Properties of Halide Perovskite Single Crystals

Abstract: Single crystals (SCs) of metal halide perovskites (MHPs) are known to possess superior properties. However, the surface of the SCs possesses a higher defect density, which can deteriorate the optoelectronic properties of SCs. Herein, we have engineered the growth of methylammonium lead tribromide SCs using (R)-3-aminopiperidine dihydrochloride (API). The modified crystals also showed improved photoresponse validated by the increased photocurrent. The modified crystal showed a highest photoresistivity of 0.47 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…However, for the device with a 200 μm electrode spacing, the photocurrent increases gradually until it reaches a saturation. The change in photocurrent shape in the I – t plot for the SC-based PDs has also been observed by others. , For example, Cho et al demonstrated that the variation of photocurrent shape can be related to the changeable dominating factor from carrier trapping at the defect states to carrier recombination under the different illumination conditions . However, the mechanism underlying the change in photocurrent shape with changing the electrode spacing is still unclear and need further investigation.…”
Section: Resultssupporting
confidence: 55%
“…However, for the device with a 200 μm electrode spacing, the photocurrent increases gradually until it reaches a saturation. The change in photocurrent shape in the I – t plot for the SC-based PDs has also been observed by others. , For example, Cho et al demonstrated that the variation of photocurrent shape can be related to the changeable dominating factor from carrier trapping at the defect states to carrier recombination under the different illumination conditions . However, the mechanism underlying the change in photocurrent shape with changing the electrode spacing is still unclear and need further investigation.…”
Section: Resultssupporting
confidence: 55%
“…92 A focused explanation of the change in photodetection properties with additives was given in our recently published work. 93,94…”
Section: Optical Propertiesmentioning
confidence: 99%
“…39 Furthermore, the presence of certain groups and carbon chain length characteristics in the additive contributes to the hydrophobicity and stability of the active layer in perovskite solar cells. 73–75 As shown in Fig. 4c, the conventional solvent ( e.g .…”
Section: Understanding the Formation Process Of Mhp Scsmentioning
confidence: 96%